Effect of E-learning Self-directed Interactive Module (E-SelfIMo) on Students’ Understanding of Earth Science Concepts - Nestor Jr Lasala; Jhonner Ricafort; Jonel Prado (Diversitas Journal, 2025)
This study sought to determine the effect of using a researcher-developed e-learning self-directed interactive module (E-SelfIMo) in enhancing the conceptual understanding of selected earth science concepts by senior high school students in the STEM strand of Sorsogon National High School. The study used a mixed-methods approach, consisting of an explanatory sequential research design and a randomized pretest-posttest control group, to compare the conceptual understanding levels of an experimental group of 30 students exposed to E-SelfIMo with 30 students in a control group. An unpaired t-test revealed no significant difference between the initial (pretest) levels of conceptual understanding of the two groups [t(58) = 0.2445, p = 0.40]. After exposure to E-SelfIMo, After exposure to E-SelfIMo, the experimental group demonstrated a significantly higher level of conceptual understanding (x̄ = 129.8, SD = 7.35) than the control group (x̄ = 112.63, SD = 9.84), t(58) = 7.66, p = 0.0001. This result was also supported by the large effect size, with a Cohen’s d value of 1.996. Qualitative analysis also supported the quantitative findings, reporting significant knowledge gains, improved learning skills, greater engagement, enhanced understanding, and positive overall learning experiences among participants due to the interactive simulations, multimedia content, and self-directed nature. The study concludes that students exposed to E-SelfIMo demonstrated significantly higher levels of conceptual understanding, indicating its positive effect on learning outcomes.